Implikasi Program Adiwiyata terhadap Karakter Peduli Lingkungan di Sekolah Dasar - Sari, Kumila; Sugiyono; Suryatin, Suryatin (Scholarly Journal of Elementary School, 2024)
This study aims to describe the implementation of the adiwiyata program and the implications of implementing the adiwiyata program on the character of caring for the environment at Public Elementary School 2 Purwoasri. This type of research is descriptive qualitative. The subject of this research is class V. The object of research is the implementation of the adiwiyata program and the character of caring for the environment. Data collection techniques used are observation, interviews, documentation and questionnaires. Data validity checking techniques use source and technique triangulation. Data analysis techniques used data reduction, data presentation and conclusion. The results showed that: (1) the implementation of the adiwiyata program at Public Elementary School 2 Purwoasri had a very good category with a score of 4.14 and was carried out according to the adiwiyata program standards from the government, (2) the implications of the adiwiyata program for the environmental care character of students in elementary schools Negeri 2 Purwoasri has a very good category with a percentage of 53% and a good category with a percentage of 47%.